2014
DOI: 10.1002/2013jg002601
|View full text |Cite
|
Sign up to set email alerts
|

Investigating carbon flux variability in subtropical peat soils of the Everglades using hydrogeophysical methods

Abstract: The spatial and temporal variability in accumulation and release of greenhouse gases (mainly methane and carbon dioxide) to the atmosphere from peat soils remains very uncertain. The use of near-surface geophysical methods such as ground penetrating radar (GPR) has proven useful during the last decade to expand scales of measurement as related to in situ gas distribution and dynamics beyond traditional methods (i.e., gas chambers). However, this approach has focused exclusively on boreal peatlands, while no st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 63 publications
(114 reference statements)
6
30
0
Order By: Relevance
“…They recorded 339 pressure periods (periods during which atmospheric pressure was consistently increasing or decreasing), but only in 28% of these periods did episodes of ebullition occur. In addition, and contrary to Tokida et al [] who found that falling atmospheric pressure was a trigger, increases in pressure can also cause ebullition [ Comas and Wright , , ; Klapstein et al , ]. It is also possible that ebullition from peat may be similar to ebullition from lakes [ Wik et al , ], where changes in atmospheric pressure trigger large degassing events that exhaust the available store of gas.…”
Section: Introductionmentioning
confidence: 99%
“…They recorded 339 pressure periods (periods during which atmospheric pressure was consistently increasing or decreasing), but only in 28% of these periods did episodes of ebullition occur. In addition, and contrary to Tokida et al [] who found that falling atmospheric pressure was a trigger, increases in pressure can also cause ebullition [ Comas and Wright , , ; Klapstein et al , ]. It is also possible that ebullition from peat may be similar to ebullition from lakes [ Wik et al , ], where changes in atmospheric pressure trigger large degassing events that exhaust the available store of gas.…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that the production and efflux of CH4 from these areas is very highly variable, both spatially and temporally (Comas and Wright, 2014). The nature of these ebullition events is such that they accumulate under flooded soils, until they have enough mass to be able to bubble up through the soil.…”
Section: Discussionmentioning
confidence: 99%
“…First, the timing and the amount of ebullition events are highly variable and unpredictable (Comas et al, 2014). The gas traps used in this experiment at LILA were relatively small compared to those used in prior studies, but they were intended to be minimally invasive to the surrounding soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations